2005
DOI: 10.1152/ajpcell.00319.2004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori lipopolysaccharide activates Rac1 and transcription of NADPH oxidase Nox1 and its organizer NOXO1 in guinea pig gastric mucosal cells

Abstract: pylori lipopolysaccharide activates Rac1 and transcription of NADPH oxidase Nox1 and its organizer NOXO1 in guinea pig gastric mucosal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 42 publications
5
93
1
Order By: Relevance
“…Several biochemical studies indicate that like gp91 phox , Nox1 activity is also governed by regulatory subunits, in this case NOXO1 and NOXA1, since Nox1-dependent reactive oxygen generation required co-expression of both NOXO1 and NOXA1 (30 -33). In addition, NOXO1 and Nox1 are coordinately expressed in the gastrointestinal tract, consistent with NOXO1 as a physiological regulatory subunit for Nox1 (31,34,35).…”
Section: Whereas P22mentioning
confidence: 53%
“…Several biochemical studies indicate that like gp91 phox , Nox1 activity is also governed by regulatory subunits, in this case NOXO1 and NOXA1, since Nox1-dependent reactive oxygen generation required co-expression of both NOXO1 and NOXA1 (30 -33). In addition, NOXO1 and Nox1 are coordinately expressed in the gastrointestinal tract, consistent with NOXO1 as a physiological regulatory subunit for Nox1 (31,34,35).…”
Section: Whereas P22mentioning
confidence: 53%
“…Noxa1 was designated as a "Nox activator" based on its homology to p67 phox , which binds to Rac1 or Rac2 and plays a more direct role in modulating oxidase activity. Recent evidence suggests that Rac1 also regulates Nox1 most likely through GTP-dependent interactions with the Nox activator, Noxa1 [16][17][18][19] We showed that the association of Noxa1 with the plasma membrane depends on its interaction with Noxo1 [17]. These structural and functional similarities between the Nox and phox regulators may explain why Noxo1 and Noxa1 can function in partially compensating for p47 phox and p67 phox in supporting Nox2 activity [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 60%
“…platelet-derived growth factor induce the expression of Nox1 in vascular smooth muscle cells [28][29][30][31][32][33]. Moreover, it has been demonstrated that mitochondrial-derived ROS positively regulate the expression of Nox1 [34], and that LPS-stimulated expression of Nox1 was profoundly suppressed in the presence of antioxidants [35]. Thus, the expression of Nox1 appears to be regulated by complex systems which differ according to the kind of cells.…”
Section: Discussionmentioning
confidence: 99%